Organizational Climate Effects on the Relationship Between Emotional Labor and Turnover Intention in Korean Firefighters - Hye-Yoon Ryu; Dae-Sung Hyun; Da-Yee Jeung; Chang-Soo Kim; Sei-Jin Chang (Elsevier, 2020)
Background: The purpose of this study is to examine the combined effects of organizational climate (OC) with emotional labor (EL) on turnover intention in Korean firefighters. Methods: The data were obtained from the study Firefighters Research: Enhancement of Safety and Health. A total of 4,860 firefighters whose main duty was providing "emergency medical aid" were included. To examine the effects of OC on the relationships between five subscales of EL and turnover intention, four groups were created using various combinations of OC ("good" vs. "bad") and EL ("normal" vs. "risk"): (1) "good" and "normal" (Group I), (2) "bad" and "normal" (Group II), (3) "good" and "risk" (Group III), and (4) "bad" and "risk" (Group IV). Multivariate logistic regression analyses were performed to estimate the risk of turnover intention for the combinations of OC and EL. Results: The results showed turnover intention was significantly higher in the group with "bad" OC (17.7%) than in that with "good" OC (7.6%). Combined effects of OC and EL on turnover intention were found in all five subscales with the exception of Group I for emotional demands and regulation. Groups II, III, and IV were more likely to experience risks of turnover intention than Group I (p for trend <0.001). Conclusions: A positive and cooperative OC plays a role in decreasing the risk of turnover intention and in attenuating the negative effects of EL on turnover intention in firefighters.